The causes of mistakes in the translation of German pronouns into Ukrainian - Oleksandra Shadrina; Pavlo Shopin (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ., 2024)
The article analyzes the causes of mistakes made by students when translating German pronouns into Ukrainian and the ways to avoid such mistakes. The relevance of the study lies in the fact that students regularly make mistakes when translating German pronouns into Ukrainian, which leads to misunderstanding and significantly decreases the quality of the translated text. This research paper will help make translation training more effective and improve the results of students’ translation work. The materials of the study are translations from German into Ukrainian made by student translators as part of the work of the academic student circle Translation Practice in Action in the Department of Applied Linguistics, Comparative Language Studies and Translation at the Dragomanov Ukrainian State University. The research methodology is based on the analysis and comparison of original texts, draft, and published translations. This approach made it possible to identify a number of mistakes and categorize them into the following groups of German pronouns: personal pronouns, the indefinite personal pronoun man, possessive pronouns, interrogative pronouns, the negative pronoun kein, the reflexive pronoun sich, and the demonstrative and relative pronouns. The study resulted in the identification of the main causes of mistakes in the translation of German pronouns into Ukrainian: misunderstanding or inattention to the context; the same forms of the indicative and relative pronouns and articles in German; the ability of the pronoun man to indicate a specific person; the ambiguity of German pronoun forms (e.g., sie, ihr); changes during translation in the grammatical gender, number and case of the pronouns and the nouns to which they refer. To avoid such mistakes, translators should carefully read and understand the original text and context, take into account the specific meaning and function of pronouns, and consider the differences in grammatical gender, number, and case between Ukrainian and German nouns and pronouns. The translation of German pronouns into Ukrainian requires a comprehensive understanding of not only language structures but also the context in which they are utilized.